Waterborne disease outbreaks associated with environmental and undetermined exposures to water — United States, 2013‐2014. Issue 1 (21st December 2017) - McClung, R. Paul; Roth, David M.; Vigar, Marissa; Roberts, Virginia A.; Kahler, Amy M.; Cooley, Laura A.; Hilborn, Elizabeth D.; Wade, Timothy J.; Fullerton, Kathleen E.; Yoder, Jonathan S.; Hill, Vincent R.
Abstract : This article describe outbreaks of infections, including legionella and giardia, linked to environmental exposure to water, such as aerosol spread from cooling towers, industrial or agricultural processes, decorative displays, and consumption of water from natural sources.